Photon-upconversion barcode for monitoring an enzymatic reaction with a fluorescence reporter in droplet microfluidics - Hlaváček, Antonín; Křivánková, Jana; Pizúrová, NaděŽda; Václavek, Tomáš; Foret, František (The Analyst, 2020)
We report luminescent photon-upconversion barcodes for indexing the chemical content of droplets. The barcode is compatible with the simultaneous detection of fluorescence. The encoding and decoding of the initial concentration of enzyme β-galactosidase and substrate 4-methylumbelliferyl β-d-galactopyranoside are described. The fluorescent product 4-methylumbelliferone is detected simultaneously with the barcode.
Keywords: Microfluidics; beta-Galactosidase; Galactose; beta-galaktosidasa; galaktosa; fluorescenční barviva; Fluorescent Dyes; mikrofluidika